Labyrinthine ossification secondary to childhood bacterial meningitis: implications for cochlear implant surgery. - Becker, T S; Eisenberg, L S; Luxford, W M; House, W F (American Journal of Neuroradiology, 1984)
Of 20 children who underwent cochlear implantation for profound sensorineural hearing loss secondary to bacterial meningitis, 14 had round-window and cochlear ossification at surgery. Preoperative polytomography demonstrated ossification in 11 of these. The incidence of ossification was highest after meningitis secondary to pneumococcal pneumonia. In only one of four children with severe ossification of the labyrinth was implant surgery unsuccessful. Preliminary results indicate that mild labyrinthine ossification is not a contraindication to cochlear implantation.